Financial Behavior of MSMEs: Do Financial Knowledge, Financial Attitude, and Financial Risk Tolerance Matter? - Raya Anandita Puspaning Adhisti; Bima Cinintya Pratama; Azmi Fitriati; Dwi Winarni (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2024)
This study examines the effect of financial knowledge, financial attitude, financial risk tolerance on financial behavior. The population used in this study were 252,116 MSMEs players in Banyumas, Purbalingga, Banjarnegara, Cilacap and Kebumen Regencies. The sample calculation method in this study is the 10 time rule of thumb technique, which uses 200 business actors in Banyumas, Purbalingga, Banjarnegara, Cilacap and Kebumen Regencies. The sampling technique used is the multistage random sampling technique for MSMEs business actors in Banyumas, Purbalingga, Banjarnegara, Cilacap, and Kebumen Regencies. This study uses the Partial Least Square Structural Equation Modeling (PLS-SEM) method which includes two models, namely the outer model and the inner model. The results of this study indicate that financial knowledge, financial attitude, financial risk tolerance have a positive impact on financial behavior.